Evaluation of antioxidant activity, phenolic content, anthocyanins, and flavonoids of fresh and dried ‘Biloxi’ blueberries - Hernández-Carrión, María; Caicedo Narvaez, Santiago (Vitae, 2022)
BACKGROUND: The phytochemical content present in blueberries has generated great interest, especially in the nutra-pharmaceutical industry, where it is known as the “super fruit” due to its prevention and treatment of neurodegenerative diseases (cardiovascular diseases, diabetes, and cancer, among others). OBJECTIVES: This study evaluated the functional potential of fresh blueberries and dried blueberries using forced convection by measuring phytochemical content to conclude if this drying technology is convenient for prolonging the product's shelf life. METHODS: For this purpose, antioxidant activity, phenolic content, total anthocyanins, and total flavonoids of ‘Biloxi’ blueberry cultivars were determined. Fresh and dried blueberries’ results were studied. Fruit extracts were analyzed to determine antioxidant activity using 2,2-diphenyl-1-picrylhydrazyl (DPPH) as a free radical, total phenolic content with Folin-Ciocalteu reagent, total anthocyanins by pH differential method, and total flavonoids by Aluminum Chloride method. RESULTS: Results for fresh blueberries yielded ranges of antioxidant activity (90.8-93.9% Free radical scavenging rate), total phenolic content (275 to 645mgGAE/100gFW), total anthocyanins content (28.55 to 43.75mgCy3G/100gFW) and total flavonoids content (159.92 to 335.75mgQE/100gFW). For the forced convection oven process, ranges of antioxidant activity (85.5-92.6% Free radical scavenging rate), total phenolic content (261 to 308mgGAE/100gFW), total anthocyanins content (4.74 to 5.12mgCy3G/100gFW) and total flavonoids content (30.66±0.38mgQE/100gFW) were obtained. CONCLUSIONS: In general, blueberries studied proved to have similar concentrations of functional properties compared to a wide variety of cultivars grown around the globe. Furthermore, higher concentrations of phytochemical content than those reported previously for strawberries, blackberries, and raspberries were evidenced. Although dried blueberries studied proved to have diminished phytochemical content, this functional component content stands out among the fruits market and give nutritional value to end consumers. Drying processes could potentially increase the commerce of blueberries by significantly reducing their perishable nature.